Treatment of stage I seminoma: 25 years of experience - Pilichowska, Małgorzata; Pęczkowski, Piotr; Rosińska-Okrasa, Dorota; Trzaska, Barbara; Skowrońska-Gardas, Anna; Demkow, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: To review management and outcomes in patients with stage I seminoma after orchidectomy. Material and methods : Between 1979 and 2004 a total 292 patients with stage I seminoma were treated with adjuvant chemotherapy or radiotherapy or were placed on surveillance. Median age at diagnosis was 36 years (range 20-69), with median follow-up 76.5 months (range 11-294). Of the patients, 200 (68.5%) were treated with adjuvant chemotherapy, 72 (24.6%) were irradiated and 20 (6.8%) were placed on surveillance. Results: The probability of 5-year overall survival and relapse-free survival for the entire group was 100% and 95.1% respectively. The 5-year relapse-free survival for adjuvant chemotherapy was 97.2%, for radiotherapy 94.6%, and 31.4% for the surveillance group. Of 24 (8.4%) patients who had relapse in lymph nodes and/or internal organs, 14/20 patients were in the surveillance group. All patients who had a relapse were salvaged successfully with chemotherapy. The toxicity of chemotherapy and radiotherapy was acceptable. No severe reactions were observed. Conclusion : Our results confirm the excellent prognosis for patients with stage I seminoma after orchidectomy treated with adjuvant chemotherapy or radiotherapy. The high rate of relapse in our surveillance group suggests the necessity of adjuvant treatment.